(Inventory of Ants (Hymenoptera: Formicidae) in the Sarasah Uwak waterfall in Limau Manis, Padang City by Using the Bait Trap Method) - Hayyat, M.Rafiqul; Satria, Rijal (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Ants are social insects that belong to the order Hymenoptera and the family Formicidae, besides that ants act as decomposers, pollinators, and soil aerators in shady places and moist soil under rotten wood and ants are the most dominant group of terrestrial animals in the tropics. This study aims to determine the diversity of Formicidae in the Sarasah Uwak waterfall area, Limau Manis, Padang City, West Sumatra, Indonesia. This research was conducted in November 2022 using the honey bait trap method. The results obtained in this study were 88 individuals with 20 genera belonging to 4 subfamilies namely the Dolichoderinae, Formicinae, Myrmicinae and Ponerinae families. Subfamily Myrmicinae is the family with the highest number of species with 4 species while subfamilies Dolichoderinae, Formicinae and Ponerinae have 1 species each. The species with the highest number of individuals is Odontomarchus sp. with 27 individuals and the least is Acanthomyrmex sp. with 2 individuals.